Disseminated histoplasmosis with ocular adnexal involvement in seven cats. (25th August 2020) - Ewald, Margaret M.; Rankin, Amy J.; Meekins, Jessica M.; McCool, Emily S.
Abstract: Objective: To describe the clinical features, diagnosis, and treatment of disseminated histoplasmosis with conjunctival and/or nictitating membrane involvement in cats. Procedure: Medical records from seven cats with naturally acquired disseminated histoplasmosis and conjunctival and/or nictitating membrane lesions were reviewed for signalment, clinical findings, diagnostic results, treatment, and outcome. Results: Breeds included domestic shorthair (n = 5), Maine Coon (n = 1), and Siamese mix (n = 1) with four spayed females and three castrated males. Conjunctival abnormalities were identified in four cats, and nictitating membrane lesions were identified in four cats; one cat had both a conjunctival and nictitating membrane lesion. Cytologic evaluation of lesions identified Histoplasma capsulatum organisms in two of four cases sampled, and histopathologic evaluation identified H capsulatum in both cases in which a sample was submitted. Histoplasmosis antigen testing was positive in three of four submitted samples. Initial treatment for all cats included fluconazole (median dose: 26 mg/kg/d). Median duration of follow‐up was 11 months (range: 1‐108 months; n = 4). Resolution of ocular adnexal lesions was achieved in three cats. Two cats had relapse of disease, one of which was subsequently euthanized. One cat with concurrent feline immunodeficiency virus (FIV) infection died one month after diagnosis of histoplasmosis. Conclusions: Histoplasmosis should be a differential diagnosis for ocular adnexal inflammatory lesions in cats.